2012
DOI: 10.1371/journal.pone.0049845
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Infusion of Piperacillin/Tazobactam in Septic Critically Ill Patients—A Multicenter Propensity Matched Analysis

Abstract: The clinical efficacy of continuous infusion of piperacillin/tazobactam in critically ill patients with microbiologically documented infections is currently unknown. We conducted a retrospective multicenter cohort study in 7 Portuguese intensive care units (ICU). We included 569 critically ill adult patients with a documented infection and treated with piperacillin/tazobactam admitted to one of the participating ICU between 2006 and 2010. We successfully matched 173 pairs of patients according to whether they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 38 publications
3
16
0
Order By: Relevance
“…Grant et al reported that days of therapy were similar with both treatment groups (7.3 ± 4.8 days for continuous infusion versus 8.7 ± 7.1 days for conventional intermittent infusion, P = 0.26) [ 21 ]. This finding was also found by Patel et al [ 25 ], Lorente et al [ 26 ], Yost et al [ 29 ] and Pereira et al [ 30 ]. However, Lodise et al found that the median duration of hospital stay was significantly shorter in patients who received extended infusion therapy compared to conventional intermittent therapy (21 days versus 38 days, P = 0.02) [ 24 ].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Grant et al reported that days of therapy were similar with both treatment groups (7.3 ± 4.8 days for continuous infusion versus 8.7 ± 7.1 days for conventional intermittent infusion, P = 0.26) [ 21 ]. This finding was also found by Patel et al [ 25 ], Lorente et al [ 26 ], Yost et al [ 29 ] and Pereira et al [ 30 ]. However, Lodise et al found that the median duration of hospital stay was significantly shorter in patients who received extended infusion therapy compared to conventional intermittent therapy (21 days versus 38 days, P = 0.02) [ 24 ].…”
Section: Discussionsupporting
confidence: 84%
“…Higher clinical cure rate for the extended infusion approach was found in our study, which is an important result, indicating the merit of using the extended or continuous infusion instead of the conventional intermittent infusion approach in clinical practice. The reason for which the extended or continuous infusion leads to increased clinical cure rate may be related to the increase in the time that the drug concentrations exceed the MIC since piperacillin/tazobactam is a time-dependent antimicrobial [ 1 ], [ 12 14 ], [ 17 ], [ 19 ], [ 24 ], [ 30 ], [ 33 ], [ 34 ]. However, Falagas et al concluded no difference in clinical cure rate between extended and conventional intermittent infusion strategy after their meta-analysis [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fifteen of the included studies reported length of hospital stay (13,14,31,(33)(34)(35)37,15,16,18,23,24,26,29,30). Pooling of studies showed that patients receiving C/PI had a significantly shorter length of hospital stay (2101 patients; OR -1.27, 95% C.I -2.45-0.08, P = 0.04; Fig.…”
Section: Length Of Hospital Staymentioning
confidence: 99%
“…In spite of the well-known PK benefits of this strategy, studies have repeatedly failed to show a significant impact on mortality [12,13]. As a result further clinical studies are needed to assess the impact of this strategy, continuous infusion of b-lactams, on patient outcomes.…”
mentioning
confidence: 99%